Contemporary Bangladesh politics and Ali Riaz’s Nikhoj Gonotontra - Hasan, Md. Mahmudul (2023)
Nikhoj Gonotontra: Kortrittabder Pothrekha o Bangladesher Bhobhiswat (Missing Democracy: A Roadmap of Authoritarianism and the Future of Bangladesh [Dhaka: Prothoma Prokashon, 2021]), Ali Riaz provides an account of the systematic destruction of democratic rights and principles in contemporary Bangladesh. Through centralizing power and choking the democratic system, the government seems to have launched what Ali Riaz terms “a pandemic of repression” in the country. Semantically, the first word – nikhoj – in the title of Ali Riaz’s book also implies ‘enforced disappearance’ and reminds readers of innumerable instances of such enforced disappearances which many Bangladeshis have faced in the last decade or so.